Pengaruh Pengetahuan, Kepatuhan Dokter dan Peran Manajemen Rumah Sakit Terhadap Kelengkapan Pengisian Rekam Medis Elektronik Rawat Jalan di Rumah Sakit Dr Sobirin Kabupaten Musi Rawas Provinsi Sumatera Selatan - Shinta Anggraini; Sumeidi Kadarisman; Rulia Rulia; Rukhiyat Syahidin; Vip Paramarta (Universitas Pahlawan Tuanku Tambusai, 2026)
Electronic Medical Records (EMR) play a crucial role in improving healthcare service quality, patient safety, and medicolegal aspects in hospitals. However, the completeness of outpatient EMR documentation in many healthcare facilities remains suboptimal. This study aims to analyze the influence of doctors’ knowledge, doctors’ compliance, and the role of hospital management on the completeness of outpatient Electronic Medical Record documentation at dr Sobirin Hospital, Musi Rawas Regency, South Sumatra Province. This study employed a quantitative approach with an analytical research design. The study population consisted of all doctors providing outpatient services at dr Sobirin Hospital, with a census sampling technique. Data were collected through questionnaires, observations, and electronic medical record document reviews. Data analysis was conducted using multiple linear regression to examine the effects of independent variables on the dependent variable. The results showed that doctors’ knowledge, doctors’ compliance, and the role of hospital management had a significant influence, both partially and simultaneously, on the completeness of outpatient Electronic Medical Record documentation (p < 0.05). The role of hospital management demonstrated the greatest contribution to EMR completeness, followed by doctors’ compliance and doctors’ knowledge. In conclusion, enhancing doctors’ knowledge and compliance, along with strengthening hospital management roles through policies, continuous training, socialization, and reward systems, is essential to improve the completeness of outpatient Electronic Medical Record documentation.